Вплив європейських норм партисипативної демократії на підвищення рівня участі громадян України в місцевому самоврядуванні - Шумляєва, Ірина (My University, 2021)
У статті розглядаються особливості європейських правових актів, які стосуються демократичних практик партисипативної демократії, з метою їх подальшого впровадження в Україні. Зважаючи на недостатній рівень участі населення у виробленні та прийнятті публічно-управлінських рішень на локальному рівні в Україні, звернено увагу на окремі елементи партисипативного механізму залучення членів місцевих громад до місцевого самоврядування в європейських документах з питань реалізації ними права на місцеве самоврядування.

The article considers the European legal acts features concerning democratic practices of participatory democracy for their further implementation in Ukraine. Given the insufficient level of public participation in the development and adoption of public administration decisions at the local level in Ukraine, the attention is focused on some elements of the participatory mechanism of involving members of local communities in local self-government in European documents on exercising the right to local self-government.Transformation of the public service of Ukraine into an institution of social interaction in the context of the global cris.
Influence of European norms of participatory democracy on increasing the level of Ukrainian citizens participation in local government
Keywords: місцеве самоврядування; публічно-управлінські рішення; публічне управління; місцева громада; партисипативна демократія; local self-government; public administration decisions; public administration; participatory democracy